2020
DOI: 10.7554/elife.53686
|View full text |Cite
|
Sign up to set email alerts
|

DASC, a sensitive classifier for measuring discrete early stages in clathrin-mediated endocytosis

Abstract: Clathrin-mediated endocytosis (CME) in mammalian cells is driven by resilient machinery that includes >70 endocytic accessory proteins (EAP). Accordingly, perturbation of individual EAPs often results in minor effects on biochemical measurements of CME, thus providing inconclusive/misleading information regarding EAP function. Live-cell imaging can detect earlier roles of EAPs preceding cargo internalization; however, this approach has been limited because unambiguously distinguishing abortive coats (ACs) f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…This reduction of the alternate cargo on the membrane would indicate increased internalization with DAB2 removed 75 . We note that this compensation in which cargo is taken up is not found with all experimental knockdowns of adaptor proteins 88 , because the adaptors also can contribute to efficient clathrin coat assembly. Removal of PICALM, for example, reduced transferrin receptor uptake 88 .…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…This reduction of the alternate cargo on the membrane would indicate increased internalization with DAB2 removed 75 . We note that this compensation in which cargo is taken up is not found with all experimental knockdowns of adaptor proteins 88 , because the adaptors also can contribute to efficient clathrin coat assembly. Removal of PICALM, for example, reduced transferrin receptor uptake 88 .…”
Section: Resultsmentioning
confidence: 77%
“…We note that this compensation in which cargo is taken up is not found with all experimental knockdowns of adaptor proteins 88 , because the adaptors also can contribute to efficient clathrin coat assembly. Removal of PICALM, for example, reduced transferrin receptor uptake 88 . DAB2 perhaps operates more independently of AP-2 to coordinate uptake of its own cargo, as it does not need AP-2 binding to internalize LDL receptors 75 .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…However, early live-cell studies revealed that a significant portion (30–50%) of nascent CCPs fail to mature and spontaneously abort ( Ehrlich et al, 2004 ; Loerke et al, 2009 ). Several factors appear to be required to stabilize nascent CCPs, including conformational changes in AP2 ( Kadlecova et al, 2017 ) required to enhance PI(4,5)P 2 and cargo binding ( Edeling et al, 2006 ; Jackson et al, 2010 ; Kelly et al, 2014 ), cargo loading ( Ehrlich et al, 2004 ; Kadlecova et al, 2017 ; Loerke et al, 2009 ), and several “pioneer” EAPs, so named because they act during early stages of CME ( Cocucci et al, 2012 ; Ma et al, 2016 ; Ritter et al, 2013 ; Wang et al, 2020 ).…”
Section: Ccp Stabilization and Maturationmentioning
confidence: 99%
“…Among the pioneer EAPs required for early stabilization of nascent CCPs are the scaffold proteins Eps15 and Fcho1 ( Cocucci et al, 2012 ; Ma et al, 2016 ; Wang et al, 2020 ), both of which bind AP2 and each other through multiple low-affinity binding motifs and protein interaction domains. Interestingly, a recent study has revealed that Eps15 coassembles with substoichiometric amounts of Fcho1 to form phase-separated liquid-like protein droplets ( Day et al, 2019 Preprint ), a property shared by its yeast homologue, Ede1 ( Kozak and Kaksonen, 2019 Preprint ).…”
Section: Ccp Stabilization and Maturationmentioning
confidence: 99%